High electrical conductivity of double-walled carbon nanotube fibers by hydrogen peroxide treatments. Issue 1 (11th November 2015) - Morelos-Gómez, A.; Fujishige, M.; Magdalena Vega-Díaz, S.; Ito, I.; Fukuyo, T.; Cruz-Silva, R.; Tristán-López, F.; Fujisawa, K.; Fujimori, T.; Futamura, R.; Kaneko, K.; Takeuchi, K.; et al.
Abstract : H2 O2 treatment can decrease the electrical resistivity of double walled carbon nanotube fibers. The experimental observations suggest that small diameter carbon nanotubes are removed from the fiber sample. Abstract : Double-walled carbon nanotube (DWNT) fibers are of great interest due to their electrical properties and light weight, making them attractive for industrial applications including their potential use in power transmission lines. We present here a detailed study of the mechanism by which hydrogen peroxide (H2 O2 ) treatment improves the electrical transport of DWNT fibers. These fibers were immersed and sonicated in H2 O2 for several hours. Experimental results suggest that residual H2 O2 could be intercalated within intertube channels inside the bundles of DWNTs, and the oxidation treatment could also result in the removal of small diameter carbon nanotubes (CNTs). In addition, an increase in the fiber density resulted in a decrease of the electrical resistivity. The H2 O2 treatment of the DWNT fibers resulted in a metallic-like temperature dependent resistivity behavior with a transition to a semiconducting-like behavior below 30 K. We compared the effects of H2 O2 with other well-known solvents and additives commonly used to reduce the carbon nanotube fiber electrical resistivity and found that the electrical conductivity values observed in our study are as good as those obtained with thionyl chloride and iodine additives. The H2 O2 method was also used to treat other forms of carbon, where only the multi-walled carbon nanotubes doped with nitrogen exhibited a decrease in electrical resistivity. The fabrication method presented here is simple, efficient and low cost, thus making it an ideal process to be applied in the fabrication of electrically conducting carbon nanotube fibers.